Shoulder Muscle Fatigue During Repetitive Tasks as Measured by Electromyography and Near-Infrared Spectroscopy. (December 2013) - Ferguson, Sue A.; Allread, W. Gary; Le, Peter; Rose, Joseph; Marras, William S.
Objective: The objective of this study was to quantify shoulder muscle fatigue during repetitive exertions similar to motions found in automobile assembly tasks. Background: Shoulder musculoskeletal disorders (MSDs) are a common and costly problem in automotive manufacturing. Method: Ten subjects participated in the study. There were three independent variables: shoulder angle, frequency, and force. There were two types of dependent measures: percentage change in near-infrared spectroscopy (NIRS) measures and change in electromyography (EMG) median frequency. The anterior deltoid and trapezius muscles were measured for both NIRS and EMG. Also, EMG was collected on the middle deltoid and biceps muscles. Results: The results showed that oxygenated hemoglobin decreased significantly due to the main effects (shoulder angle, frequency, and force). The percentage change in oxygenated hemoglobin had a significant interaction attributable to force and repetition for the anterior deltoid muscle, indicating that as repetition increased, the magnitude of the differences between the forces increased. The interaction of repetition and shoulder angle was also significant for the percentage change in oxygenated hemoglobin. The median frequency decreased significantly for the main effects; however, no interactions were statistically significant. Conclusions: There was significant shoulder muscle fatigue as a function of shoulder angle, task frequency, and force level. Furthermore, percentage change in oxygenated hemoglobin had two statistically significant interactions, enhancing our understanding of these risk factors. Application: Ergonomists should examine interactions of force and repetition as well as shoulder angle and repetition when evaluating the risk of shoulder MSDs.